Pendekatan Cognitive-Behavioral Therapy Dengan Teknik Thought Stopping Untuk Menangani Trauma Psikologis Mahasiswa Korban Pengkhianatan: Cognitive-Behavioral Therapy Approach With Thought Stopping Technique To Handle Psychological Trauma in Student Victims of Betrayal - Haris Munandar; Anggyta Dinda Wijaya (Suluh: Jurnal Bimbingan dan Konseling, 2023)
The purpose of this research is to determine the response of psychological trauma victims of betrayal using the cognitive-behavioral therapy method with thought stopping techniques. The subjects in this study are students from one of the universities in Palangka Raya city. The research procedure is by conducting interviews using the thought stopping approach, explaining their traumatic events, and presenting the results before and after the therapy is conducted. The result of this therapy shows that the respondents have not fully been able to change their behavior and social condition because they are still in the recovery stage from the trauma they experienced. However, from a cognitive perspective, the subjects are able to suppress their negative thoughts and try to sincerely accept the incident on themselves in their affective aspect.